Behavioral-based safety management to reduce accidents in mining companies in Peru - Callupe Baldeón, Liliana (2022)
The objective of the study was to determine the relationship between behavior-based safety and the reduction of occupational accidents and incidents in the Alpayana mining company, year 2022. Methodologically, it was approached under an applied quantitative approach, with a cause-effect research design at a quasi-experimental level. The research population and sample consisted of a total of 800 accidents in the subway mine from 2018 to May 2022 subjected to data analysis and quantification. The results allowed identifying the main risks, which are: lack of organizational culture, lack of protocols and staff training to handle incidents, working under unsafe behavior. A significant relationship (p=0.01; X2=7,19) was obtained between the implementation of a behavior-based safety system and the reduction of accidents and work incidents, as well as between the different dimensions of behavior-based safety. It is concluded that the implementation of this behavior-based safety system will have a significant impact on the reduction of occupational accidents and incidents in the mining company.